A retrospective study of antimicrobial resistance pattern of Pseudomonas aeruginosa isolates from urine samples over last three years (2013-2015) - Sharma, Neetu; Gupta, Anita K.; Walia, Geeta; Bakhshi, Rupinder (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Problem of antibiotic resistance is compounding day by day because of overuse and misuse of antibiotics. There is no systematic national surveillance of antibiotic resistance and insufficient data is available to quantify the problem in our country. This study aims at studying the changing pattern of antimicrobial resistance of Pseudomonas aeruginosa isolates from patients of urinary tract infections over last three years. Methods: A retrospective, record based study carried out based on the records of C/S (Culture sensitivity) reports of indoor patients, during past three years (2013 - 2015). The types of organisms causing urinary tract infections were noted and the drugs still effective for the Pseudomonas aeruginosa were noted. Results: Pseudomonas aeruginosa is inherently resistant to many antimicrobial agents. Analysis of the results year wise indicated that the lowest percentage of resistance manifested against imipenem was 14%, 24.48% and 20.99% for the years 2013-2015. Resistance for fluoroquinolones decreased over the three consective years from 84.67% (2013) to 78.27% (2015). Over the successive years, the resistance to ceftriaxone tends to increase from 80% (2013) to 92.59% (2015). C/S reports showed on an average 69% were resistant to aminoglycosides. Multi drug resistant pseudomonas percentage resistant to fluoroquinolones, third generation cephalosporines and aminoglycosides were 78% (2013), 78.33% and 80.33% (2015) over the consective years. Conclusions: The antimicrobial resistance patterns are constantly evolving and vary from region to region it has become a necessity to do constant antimicrobial sensitivity surveillance. This will help clinicians to provide safe and effective empirical therapies.